Fluctuations of populations of the pin nematode Paratylenchus projectus under selected potato management practices - Potter, J.W.; McKeown, A.W. (Phytoprotection, 2002)
Experiments on the distribution and survival of pin nematode Paratylenchus projectus in potato growing systems and on its control by various mechanisms are described. Preferable management strategies for the pin nematode include the use of flax or a high-glucosinolate mustard or canola, the use of 'Trudan 8' sudangrass to add organic matter into the soil, and shallow but thorough tillage of a sandy soil in the fall or in early spring to disrupt the soil. In general, many grasses and legumes should be avoided as cover crops.